PRO-Act: a healthcare provider workshop outlining the added value of implementing PROs in routine HIV practice - António Antunes; Ricardo Racha-Pacheco; Catarina Esteves; Ana Tavares; Josefina Mendez; Patrícia Pacheco; Duncan Short (SpringerOpen, 2023)
Abstract Patient Reported Outcomes (PROs) are an evidenced way of adding value to routine clinical care. As a source of unique information on the effect of a medical condition and its treatment from the patients' perspective (Mercieca-Bebber et al. in Patient Relat Outcome Meas 9: 353-367, https://doi.org/10.2147/PROM.S156279 , 2018), PROs allow for an improved assessment in routine clinical care of symptoms, side effects, functional outcomes (physical, sexual, social, emotional, cognitive functioning), and health-related quality of life (HRQoL). By helping to align healthcare providers' interventions with what matters most to the patient, PROs contribute to the individualized choice of Anti-Retroviral Therapy (Carfora et al. in PLoS ONE 17(4): e0267030, https://doi.org/10.1371/journal.pone.0267030 , 2022) as a paramount component of tailored and person-centred care management, in routine clinical practice. This article outlines a practical framework and process tested in Portugal to raise awareness of PROs' added value, and to help guide first steps in the implementation and seamless integration of PROs, in routine HIV care.